2018
DOI: 10.21577/0103-5053.20180245
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Sensors Based on Cu-Doped Carbon Quantum Dots for the Detection of Rutin

Abstract: In this paper, Cu-doped carbon quantum dots (Cu-CQDs) were prepared by carrying out thermolysis of Na 2 [Cu(EDTA)] and hydroxylamine hydrochloride at 300 °C for 2 h. The asprepared Cu-CQDs were characterized by UV-Vis, Fourier transform infrared (FTIR) spectroscopy, transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD). The Cu-CQDs exhibited good fluorescence property, high stability, excitationdependent emission behavior and a quantum yield of 9.8%. More si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
(37 reference statements)
1
12
0
Order By: Relevance
“…Both morphological structure characteristics are consistent with what is reported for these new carbon-based nanomaterials, where the size corresponds to a value below 10 nm. 44,45 Figure 2. (a) XRD analysis showing the efficiency of the purification method in removing impurities, leading to high luminescent CBDs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both morphological structure characteristics are consistent with what is reported for these new carbon-based nanomaterials, where the size corresponds to a value below 10 nm. 44,45 Figure 2. (a) XRD analysis showing the efficiency of the purification method in removing impurities, leading to high luminescent CBDs.…”
Section: Resultsmentioning
confidence: 99%
“…It could be further deconvoluted into three bands, corresponding to sp 2 (C=C/C-C, 283.32 eV), sp 3 (C-O, 284.76 eV), and carbonyl carbons (C=O, 285.94 eV). 12,44 The use of demineralization and desulfurization agents play an important role to remove ashes, silica, and sulfur as described by Banar et al 38 Also, using oxidant agents produce a carboxyl groups and hydroxyl in CBD material, becoming soluble in water, according to assignment of FTIR and XPS of this material. The addition of NaOH after this process is very important to precipitate metal hydroxides which remained in the sample after treatment with KMnO 4 (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Quant dots were the name given to these fluorescent carbon nanoparticles. In 2006, a synthetic method for producing quantum dots carbon with a higher fluorescence emission through the transition surface was introduced (Figure 2) (Wang et al, 2019a).…”
Section: Metal Ion Detectionmentioning
confidence: 99%
“…Both rutin and quercetin are major sources of pharmaceutical products for phytotherapy [19,20]. Many studies revealed rutin possesses anti-inflammatory, anticarcinogenic, neuroprotection, antiproliferative, antimetastatic, and antioxidative stress effects via inhibiting lipid peroxidation and amelioration of oxidative stress [21,22]. Reactive oxygen species (ROS) can damage DNA, chromosomal mutations, unregulated gene expressions, cell division, and cell growth.…”
Section: Natural Occurrence and General Pharmacological Effects Of Rutinmentioning
confidence: 99%